An integrated development environment for the NS-2 Network Simulator - Oliveira, D. M.; Cruz, R. S.; Salgueiro, R. J. P. B.; Rocha, T. (Scientia Plena, 2012)
Simulation is one of the most important tools used for modeling and performance evaluation of computer systems. Among the various options for languages and simulation packages available for the area of computer networks, the NS-2 stands out for being the most popular open source tool used. However, the NS-2 does not provide a good infrastructure for the development of simulation projects. This paper proposes an integrated development environment (IDE) with a rich graphical interface that support project creation, distributed or sequential execution and result project recovery under the form of charts. The developed tool is used in a real project simulation performance evaluation of an access point for mobile devices via a Bluetooth connection. With this case study, the benefits introduced with the use of IDE in conjunction with the NS-2 are demonstrated.